Konstruksi Baru & Pengembangan Wisata Religi di DKI Jakarta (Universitas Negeri Jakarta, 2019)
This study examines and analyzes the new construction of the concept of religious tourism through mosques with the history of Islam behind it. In addition to tombs, mosques become a destination for religious tourism locations, namely religiously motivated religious tourism, to get closer to God Almighty. Visiting mosques can be a means to improve the side of individual spirituality, through aspects of worship that can be done in it; Also, able to promote religious understanding through a variety of religious studies that are routinely carried out. But apparently, some mosques have historical stories of the development of Islam in them. Through this story, the pilgrims were able to understand the role of the mosque in attaching the unity of the surrounding community against the invaders; mosques become the center of civilization. Through new construction and the development of religious tourism, the mosque insists that it is not only a place of worship; but also, as the center of civilization; community unifying area. This study uses a qualitative descriptive method with data collection in the form of observation, interviews, documentation, and literature studies related to mosques in the DKI Jakarta area. The findings in this study indicate the destination of mosques in the DKI Jakarta area, which can show its identity as the center of civilization; as a unifying society in the fight against invaders in the past.